A subfamília Euphorinae (Hymenoptera, Braconidae) em gradientes altitudinais da região Sudeste brasileira, incluindo considerações taxonômicas - Almeida, Luis Felipe Ventura de (Universidade Federal de São Carlos, 2018)
Insects constitute a large fraction of the biodiversity and are fundamental to the functioning of terrestrial ecosystems. Among the insects, one of the most speciose and important groups are the parasitic Hymenoptera, which act to control populations of various phytophagous insects, and are therefore of great ecological and economic importance. Despite its recognized importance they are still poorly studied, especially in the neotropical region, where the knowledge about this group is quite limited. A large fraction of the species is not yet formally described and very little is known about their distribution patterns. The present study aims to contribute to the taxonomic and ecological knowledge of the subfamily Euphorinae (Hymenoptera, Braconidae) in Brazil, focusing on the diversity present at areas with altitudinal gradients in southeastern Brazil. Four altitudinal gradient areas were studied: 1) Serra da Bocaina National Park, São José do Barreiro, SP 2) Itatiaia National Park, Itatiaia, RJ 3) Alto-Montana Natural Heritage Private Reserve, Itamonte, MG and 4) Serra do Japi Biological Reserve, Jundiaí, SP . A total of 743 specimens belonging to the subfamily Euphorinae were found, distributed in 16 genera and 125 species, a considerably large number when compared to the 22 formally described species recorded in Brazil. The genera Leiophron, Meteorus and Microctonus were dominant in the samples representing 40.38%, 28.40%, 16.29% of the total specimens respectively, and 37, 33 and 21 morphospecies. Significantly more females were found than males, and the sex ratio varied with altitude. The Malaise traps represented about two-thirds of all material sampled, however the genera Chrysopophtorus, Pygostolus and Zele were caught only in light traps and the genus Holdawayella in Moericke traps. Considering the totality of the material obtained the highest diversity was found in the altitude range between 1200 and 1700m. Twelve new species are described and illustrated, in the genera Centistes (two species), Centistoides (one species), Ecclitura (one species), Marshiella (one species), Meteorus (two species), Pygostolus (two species) and Streblocera (three species).
Keywords: Diversidade; Gradiente altitudinal; Taxonomia; Euphorinae; Parasitoide; Braconidae; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES